PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN MENGGUNAKAN METODE INDEX CARD MATCH (ICM) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III C SD NEGERI 188 PEKANBARU - Cori Cornellia; Mahmud Alpusari; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study was to improve the learning outcomes sciece of the third grade students of Pekanbaru 188 Elementary School by applying the take and give type of cooperative learning by using a method index card match. The type of research used is classroom action research carried out for two cycles. The data which are collected in this research are the teachers and students activity and also the learning report. Teacher activity in the cycle I of the first meeting obtained score of 15 (62.50%)) with sufficient category and at the second meeting obtained score of 22 (91,66%) with very good category. In addition, student activity is also increased at the first meeting of the first cycle with a percentage of 14 (58,33%) with enough category at the second meeting increasing obtained score of 20 (83.33%) with very good category in second place. cycle II meeting. Furthermore, student learning outcomes increased from the basic score to the first cycle of 15.20% with the average score of students being 67,36. In the second cycle the average score of students increased 37.04% to 80.13. From the results of the study and the type of cooperative learning by using a method index card match can improve science outcomes learning studies in class III C Pekanbaru SDN 188.Key Words: Cooperative by using a method index card match,science studies learning outcomes